EFEK HIPOTRIGLISERIDEMIA TEPUNG UMBI KIMPUL (Xanthosoma violaceum Schott.) PADA TIKUS PUTIH JANTAN - Yustisia Dian Advistasari; Etty Sulistyowati; Ika Puspitaningrum (Universitas Wahid Hasyim Semarang, 2016)
ABSTRACT Triglycerides (triacylglycerols) is the major lipid compounds in body fat and food deposits. Hypertriglyceridemia is a disorder characterized by an increase of triglyceridesconcentration in the blood. Tuber purse known as Umbi Kimpul(Xanthosomaviolaceum Schott.) is believed as a medicinal plant. This study aims to determine the effect of hipotrigliseridemiaof purse tuber flour and the effective dose. To determine the effect of hipotrigliseridemia of purse tuber flour, 30 white male Wistar rats were used and they were divided into 6 groups. Group I (normal control) was fed a standard food, group II (negative control) was given suspension CMC Na 0,5%, group III (positive control) was given suspension gemfibrozil 54 mg / kgbody weight of mice, group IV, V and VI were given pursetuber flour wtih graded dose at 270, 540 and 1080 mg / kgbody weight of mice. The Induction of hypertriglyceridemia was a mixture of standard rat food with 15% lard and 5% egg yolk of duck, as well as fructose 1.8 g / kg body weight of mice. The Induction was conducted for 50 days, unless the normal control group. Blood triglyceride levels were measured on days 0, 51 and 58. The triglyceride levels were calculated their decline percentagebefore statistically tested using SPSS statistical release16. The results showed a significant difference in the negative control group CMCNa suspension with purse tuber flour suspension. It is concluded that the purse tuber flour suspension has an effect of hipotrigliseridemia. The effective dose of pursetuber flour as hipotrigliseridemia is 270 mg / kg body weight of mice. Keywords : flour tuber kimpul, hypotriglyceride, white male rats